2005
DOI: 10.1101/gr.3783805
|View full text |Cite
|
Sign up to set email alerts
|

Long-range DNase I hypersensitivity mapping reveals the imprinted Igf2r and Air promoters share cis-regulatory elements

Abstract: Epigenetic mechanisms restrict the expression of imprinted genes to one parental allele in diploid cells. At the Igf2r/Air imprinted cluster on mouse chromosome 17, paternal-specific expression of the Air noncoding RNA has been shown to silence three genes in cis: Igf2r, Slc22a2, and Slc22a3. By an unbiased mapping of DNase I hypersensitive sites (DHS) in a 192-kb region flanking Igf2r and Air, we identified 21 DHS, of which nine mapped to evolutionarily conserved sequences. Based on the hypothesis that silenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 45 publications
2
26
0
Order By: Relevance
“…It is noteworthy that Airn and Igf2r show similar expression kinetics in mouse tissues and differentiated ESCs (Latos et al, 2009;Pauler et al, 2005). This could indicate that Airn repressor activity is limited by higher Igf2r promoter activity.…”
Section: Airn Expression Can Silence Igf2r At Any Time During Esc Difmentioning
confidence: 78%
“…It is noteworthy that Airn and Igf2r show similar expression kinetics in mouse tissues and differentiated ESCs (Latos et al, 2009;Pauler et al, 2005). This could indicate that Airn repressor activity is limited by higher Igf2r promoter activity.…”
Section: Airn Expression Can Silence Igf2r At Any Time During Esc Difmentioning
confidence: 78%
“…The active promoters of Igf2r , SNRPN , Nesp , GnasXL and Air, Nespas and Kcnq1ot1 are associated with parentalspecifi c DHS sites. No DHS sites are detected around the inactive methylated promoters of these genes (Schweizer et al, 1999;Coombes et al, 2003;Mancini-DiNardo et al, 2003;Pauler et al, 2005). At the Igf2/H19 paternal imprinting system, a DHS site is present at the active, unmethylated but not at the inactive, methylated promoter of the H19 gene (Khosla et al, 1999).…”
Section: Nucleosome Densitymentioning
confidence: 84%
“…It is also possible for 3′-3′ or fully overlapped transcripts to compete for or share common transcriptional factor binding sites, since genomic regions harboring regulatory elements can stretch as much as 1 Mb in either direction from the transcription unit [136]. For example, results from DNase I footprinting suggest that imprinted Igf2R and Air promoters appear to share common cis-regulatory elements [137]. In addition, one recent genome-scale study showed that about 4% of CREB binding sites are located at the 3′ end of the target genes, many of which have known antisense transcripts [138].…”
Section: Class I Model: Transcriptional Regulation Independent Of Ovementioning
confidence: 99%